2012
DOI: 10.1021/jm300951u
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Hinge Glycine Flip and the Activation Loop: Novel Approach to Potent p38α Inhibitors

Abstract: The p38 MAP kinase is a key player in signaling pathways regulating the biosynthesis of inflammatory cytokines. Small molecule p38 inhibitors suppress the production of these cytokines. Therefore p38 is a promising drug target for novel anti-inflammatory drugs. In this study, we report novel dibenzepinones, dibenzoxepines, and benzosuberones as p38α MAP kinase inhibitors. Previously reported dibenzepinones and dibenzoxepines were chemically modified by introduction of functional groups or removal of a phenyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…For example, the DFG-motif of P38α co-crystallized with dibenzoxepinone (PDG: 4L8M) adopts an intermediate conformation in which the DFG-Asp side chain directly interacts with the ligand. 17 Structures in the DFG-in, DFG-out, and intermediate conformations account for 75.6, 7.3, and 17.1% of all kinase structures, respectively. Moreover, the fraction of crystal structures in the DFG-out conformation varies between serine/threonine (S/T) kinases and tyrosine (Y) kinases (Figure 2 A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, the DFG-motif of P38α co-crystallized with dibenzoxepinone (PDG: 4L8M) adopts an intermediate conformation in which the DFG-Asp side chain directly interacts with the ligand. 17 Structures in the DFG-in, DFG-out, and intermediate conformations account for 75.6, 7.3, and 17.1% of all kinase structures, respectively. Moreover, the fraction of crystal structures in the DFG-out conformation varies between serine/threonine (S/T) kinases and tyrosine (Y) kinases (Figure 2 A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Most studies of p38 MAPK in AD pathologies have been investigated using indirect inhibitors. In addition, most studies using direct p38 MAPK inhibitors have used SB203580 ( 5 ) and other commercially available inhibitors with lower potency and selectivity than recently reported p38 MAPK inhibitors such as 34 and compound 35 ( Figure 11 ) [ 156 , 157 , 158 , 159 , 160 , 161 ]. In particular, a series of p38 MAPK inhibitors, 34 and 35 , possessing diaryl ketone moieties have been reported to make potent bindings with the p38 MAPK, due to their carbonyl oxygens which can induce glycine flip, leading to double hydrogen bonding to Met109 and Gly110 in the hinge region.…”
Section: Discussionmentioning
confidence: 99%
“…A research group at Eberhard-Karls-University Tubingen previously reported this approach to enhance enzymatic inhibitory activity of dibenzepinone-based p38 MAP kinase inhibitors. [28] As highlighted in Figure 1, the structures of BMS-582949, [29] BCT-197, GW856553, PH-797804, and AZD-7624 share common fragments, including the p-methylbenzamide moiety, which frequently binds to the back pocket of p38 MAP kinase. Using X-ray crystallography, a group of researchers at GSK demonstrated that the amide group of the methylbenzamide moiety of biphenyl amide derivatives has hydrogen bonding interactions with Glu71 and Asp168 in the back pocket of the enzyme (Figure 4 lower part).…”
Section: Introductionmentioning
confidence: 99%
“…Using information from the three‐dimensional structure of the protein‐ligand complex, we employed an expanding approach by targeting some of the interactions of the ligand with the back pocket of the enzyme for generating a novel p38 MAP kinase inhibitor scaffold. A research group at Eberhard‐Karls‐University Tubingen previously reported this approach to enhance enzymatic inhibitory activity of dibenzepinone‐based p38 MAP kinase inhibitors . As highlighted in Figure , the structures of BMS‐582949, BCT‐197, GW856553, PH‐797804, and AZD‐7624 share common fragments, including the p ‐methylbenzamide moiety, which frequently binds to the back pocket of p38 MAP kinase.…”
Section: Introductionmentioning
confidence: 99%